Do Dehydroepiandrosterone (DHEA) and Its Sulfate (DHEAS) Play a Role in the Stress Response in Domestic Animals? - Gabai, Gianfranco; Mongillo, Paolo; Giaretta, Elisa; Marinelli, Lieta (Frontiers in Veterinary Science, 2020)
In animal husbandry, stress is often associated with poor health and welfare. Stress occurs when a physiological control system detects a state of real or presumptive threat to the animal’s homeostasis or a failure to control a fitness-critical variable. The definition of stress has mostly relied on glucocorticoids measurement, even though glucocorticoids represent one stress-response system, the hypothalamus-pituitary-adrenocortical axis, which is not precise enough as it is also related to metabolic regulation and activated in non-stressful situations (pleasure, excitement and arousal). The mammal adrenal can synthesize the androgenic steroid dehydroepiandrosterone (DHEA) and its sulfate metabolite (DHEAS), which have been associated to the stress response in several studies performed mostly in humans and laboratory animals. Although the functions of these steroids are not fully understood, available data suggest their antagonistic effects on glucocorticoids and, in humans, their secretion is affected by stress. This review explores the scientific literature on DHEA and DHEAS release in domestic animals in response to stressors of different nature (inflammatory, physical or social) and duration, and the extra-adrenal contribution to circulating DHEA. Then, the potential use of DHEA in conjunction with cortisol to improve the definition of the stress phenotype in farmed animals is discussed. Although the focus of this review is on farmed animals, examples from other species are reported when available.